2015
DOI: 10.1103/physrevb.92.224403
|View full text |Cite
|
Sign up to set email alerts
|

In situsmall-angle x-ray and nuclear resonant scattering study of the evolution of structural and magnetic properties of an Fe thin film on MgO (001)

Abstract: Growth of magnetron sputtered Fe films on clean single crystalline MgO (001) substrate has been studied using in situ grazing incidence small angle x-ray scattering (GISAXS) and grazing incidence nuclear resonant scattering (GINRS) measurements. While GISAXS provides information about morphological changes, GINRS provides information about structural and magnetic properties, thus making it possible to correlate the evolution of magnetic properties with that of morphology and structure of the film. The film exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…It may be noted that when the thickness of the film is very small, typically below the percolation limit (about 2 nm for Fe), the film comprises of isolated grains and therefore the stress produced during the growth may lead to distortion in the cubic symmetry resulting in larger QS. Emergence of such QS was also observed in ultrathin Fe films during the in-situ growth of Fe films on MgO(001) [83] at 300 K. The gradual reduction in QS with increase in the thickness indicates that the system transforms towards cubic symmetry which is also evident from our N K-edge XANES measurements presented in section 3.3. More details about the influence of film thickness on such stress are discussed in section 3.4.…”
Section: 2supporting
confidence: 73%
“…It may be noted that when the thickness of the film is very small, typically below the percolation limit (about 2 nm for Fe), the film comprises of isolated grains and therefore the stress produced during the growth may lead to distortion in the cubic symmetry resulting in larger QS. Emergence of such QS was also observed in ultrathin Fe films during the in-situ growth of Fe films on MgO(001) [83] at 300 K. The gradual reduction in QS with increase in the thickness indicates that the system transforms towards cubic symmetry which is also evident from our N K-edge XANES measurements presented in section 3.3. More details about the influence of film thickness on such stress are discussed in section 3.4.…”
Section: 2supporting
confidence: 73%
“…Thus, the additional thickness of 0.4 nm has not added to the intensity of prepeak, suggesting that 0.3 nm is the upper limit to the thickness of the interfacial oxide layer. earlier study on an identically prepared structure, it was found using nuclear forward scattering that an interfacial layer of ~0.4 nm thickness possesses an average hyperfine field of 30.8 T, as against 33 T for bcc iron metal [48,49]. This was taken as an evidence for hybridization of Fe with oxygen in the interfacial region.…”
Section: Fe On Mgo (001) Substratementioning
confidence: 97%
“…the long acquisition time which precludes an acceptable temporal resolution, compatibility with the deposition conditions etc.). Therefore, various strategies of real-time and in situ X-ray scattering experiments have been developed in the past (Vegso et al, 2012;Gibaud et al, 2004;Sharma et al, 2015;Renaud et al, 2009;Siffalovic et al, 2007;Hodas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%